WE WERE SAILING INTO UNCHARTED WATERS: FLAWS IN THE APPLICATION OF CANADA’S CRIMES AGAINST HUMANITY AND WAR CRIMES ACT - Nerenberg, Marc; Larochelle, Philippe (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2014)
In Canada’s two trials to date under the Crimes Against Humanity and War Crimes Act, serious flaws in the application of the Act have emerged, in particular regarding the framing of the indictment. In prior proceedings at the ICTR and ICTY, the indictments contained detailed recitations of the facts, including the specific “constitutive crimes” for which trials on the “chapeau crimes” of genocide, war crimes and crimes against humanity were held, and in which convictions and acquittals were based on these indicated “constitutive crimes”. In Canada, the indictments merely indicated the “chapeau crimes” and not the “constitutive crimes”, making it impossible for an accused to know precisely for what he is charged, negatively affecting trial preparation, and impossible to determine if a jury is actually unanimous on any given “constitutive crime”, effectively rendering illusory the right to a jury trial. The authors argue that the Canadian indictments foster a fundamental misunderstanding of the essential elements needed to prove the international crimes of genocide, war crimes and crimes against humanity, compromising the possibility of holding a fair trial under the Act.